1985
DOI: 10.1093/nar/13.13.4765
|View full text |Cite
|
Sign up to set email alerts
|

Conserved sequences in both coding and 5′ flanking regions of mammalian opal suppressor tRNA genes

Abstract: The rabbit genome encodes an opal suppressor tRNA gene. The coding region is strictly conserved between the rabbit gene and the corresponding gene in the human genome. The rabbit opal suppressor gene contains the consensus sequence in the 3' internal control region but like the human and chicken genes, the rabbit 5' internal control region contains two additional nucleotides. The 5' flanking sequences of the rabbit and the human opal suppressor genes contain extensive regions of homology. A subset of these hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…These studies provide evidence that tRNA [ser]sec has a twofold function of serving as a carrier molecule upon which selenocysteine is synthesized and as a direct donor of selenocysteine to protein (e.g., glutathione peroxidase) in response to specific UGA codons (18). The gene encoding tRNA[SerlSec occurs in single copy in human (22,27), rabbit (28), and chicken (11) genomes, and its expression is controlled by multiple 5' extragenic regulatory elements (17). Transcription of this unique tRNA begins at the first nucleotide within the gene (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies provide evidence that tRNA [ser]sec has a twofold function of serving as a carrier molecule upon which selenocysteine is synthesized and as a direct donor of selenocysteine to protein (e.g., glutathione peroxidase) in response to specific UGA codons (18). The gene encoding tRNA[SerlSec occurs in single copy in human (22,27), rabbit (28), and chicken (11) genomes, and its expression is controlled by multiple 5' extragenic regulatory elements (17). Transcription of this unique tRNA begins at the first nucleotide within the gene (16).…”
mentioning
confidence: 99%
“…We have previously shown that the human (22,27), rabbit (28), and chicken (11) tRNA [Ser]sec genes occur in single copy within their respective genomes. The tRNA[ser]sec gene copy number was examined within the genomic DNA of X. laevis, D. melanogaster, and C. elegans (Fig.…”
mentioning
confidence: 99%
“…In fact, two opal suppressor phosphoserine tRNAs that arise from a single gene (9)(10)(11) have been identified (7). These isoacceptors manifest several distinctive characteristics that set them apart from all other eukaryotic tRNAs.…”
mentioning
confidence: 99%
“…(v) They contain an extra unpaired nucleotide within the stem of loop IV (6)(7)(8). (vi) They differ in their primary sequences by several pyrimidine transitions including one in the wobble position of their anticodons (7), and these transitions must occur post-transcriptionally since both species are encoded by the same gene (9)(10)(11)(12). (vii) They are phosphorylated on their serine moiety by a kinase to form phosphoseryl-tRNA (7,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation